Assessment of different cut-off values of the ELISA-Typhimurium for the discrimination of swine herds with Salmonella isolation - Kich, Jalusa Deon; Costa, Eduardo de Freitas; Triques, Nelise Juliane; Niogueira, Mariana; Costa, Osmar Antonio Dalla; Coldebella, Arlei; Kummer, Aline; Cardoso, Marisa (Semina: Ciências Agrárias, 2016)
Salmonella control programs require the classification of positive herds according with the prevalence of infected pigs. This must be based on diagnostic methods that are reliable, accurate and cost effective. Since serological methods fulfill most of these prerequisites, many countries have adopted indirect ELISA tests to discriminate herds, based on their seroprevalence. In view of that, an in-house indirect ELISA test (ELISA-Typhimurium) previously developed proved to be able to detect sera antibodies against the most prevalent serovars of Salmonella found in Brazilian pig farms. This study aimed to assess different cut-off values of the ELISA-Typhimurium in terms of their correlation with Salmonella isolation results at the herd level. Blood and mesenteric lymph node or rectal swabs were taken from 56 slaughter and 14 grower batches from different farms. Serum was tested using the ELISA-Typhimurium at different cut-off points (OD: 6.87%-40%). A total of 55 slaughter batches had at least one Salmonella-positive sample, and the within-herd prevalence was 64.9% (SEÂ±24.8). All 14-grower batches were negative on Salmonella isolation. The logistic regression demonstrated that at 20% OD the ELISA-Typhimurium test is the best model to predict Salmonella isolation frequency at the herd level. At this cut-off point, the test may be a helpful tool for discriminating Salmonella infected herds.